Meningkatkan Kemampuan Komunikasi Matematis Siswa dengan Implementasi Model Pembelajaran Missouri Mathematics Project (MMP) - Nike Astiswijaya (Jurnal Pendidikan Matematika:Judika Education, 2020)
One of the goals of mathematics learning is that students can develop communication skills (Permen Number 22 of 2006). MMP model is one model that can improve student’s mathematical communication skills. Based on this, a research was conducted on the implementation of the MMP learning model with the aim to describe student learning activities in mathematics learning using the MMP learning model and to describe mathematical communication skills in mathematics learning after using the MMP learning model. The research method is descriptive. Population in this research were all students of class XI of SMK YP Gajah Mada Palembang in the 2018/2019 and the samples of this research were students of class XI TKRO 3. Data collection techniques using documentation, observation and test techniques. The data obtained were analyzed using descriptive statistical techniques namely average and percentage. The results showed that the learning activities of students in learning mathematics using the MMP model in class XI TKRO 3 were in the good category. Mathematical communication skills of students in learning mathematics after using the MMP learning model in class XI TKRO 3 are in the good category. Key word: MMP Model learning, communication mathematics skill